Ultrastructural Detection of Surface Exposed Phosphatidylserine on Activated Blood Platelets - Stuart, M C A; Bevers, E M; Comfurius, P; Zwaal, R F A; Reutelingsperger, C P M; Frederik, P M (Thrombosis and Haemostasis, 1995)
Phosphatidylserine (PS) is normally restricted to the inner leaflet of the plasma membrane of cells (including blood platelets). Upon cell activation PS may become exposed to the outer surface of the cell. Cell membranes with surface exposed PS at the outside form a catalytic surface for coagulation reactions. When platelets are activated with ionophore or with thrombin in combination with thapsigargi, calcium induced scrambling of phospholipids takes place, resulting in PS exposure. Concomitant with PS exposition structural changes take place. On resting and activated platelets we combined the immunocytochemical detection of surface exposed PS with (ultra)structural information. Blood platelets were activated in the presence of annexin V, a protein which binds to PS in the presence of Ca2+. Annexin V was found to bind to lipid bilayers containing more than 5 mole % PS as estimated by binding of fluorescent-labelled annexin V to liposomes with varying PS concentrations. After vitrification, freeze-substitution and embedding of the platelets, annexin V was located on ultra thin sections, as detected by an anti-annexin V antibody and gold labelled protein A. Upon activation, the platelets show two different forms; irregular platelets with unchanged cytoplasm and round cells with apparently diluted cytoplasm. Activation with ionophore initially resulted in both forms, but after ten minutes only round platelets with diluted cytoplasm were observed. Both forms of these platelets as well as the microvesicles were found to be annexin V positive. However upon activation with thrombin in combination with thapsigargin, only the round cells with diluted cytoplasm and microvesicles were annexin V positive, whereas platelets with unchanged cytoplasm, even when microvesicles are present, are negative for annexin V.